2011
DOI: 10.1143/jjap.50.091102
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline In–Ga–Zn–O Density of States and Energy Band Structure Calculation Using Density Function Theory

Abstract: The density of states (DOS) and energy band structure of crystalline In-Ga-Zn-O (c-IGZO) and the impact of point defects on its electronic structure are investigated by first-principles calculations based on the density function theory. The calculated DOS showed that the p-orbitals of the oxygen atoms mostly contribute to the valance band maximum (VBM) of c-IGZO. The conduction band minimum (CBM) is dominated by s-orbitals of the Zn/Ga mixture atoms, while the In atoms have the largest spatial spread of wave f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 33 publications
(47 reference statements)
3
32
0
Order By: Relevance
“…Finally, the single phase of IGZO was formed when the calcination temperature reached 1100 C. All reflections can be indexed as the rhombohedral symmetry structure [JCPDS No. 38e1104] [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the single phase of IGZO was formed when the calcination temperature reached 1100 C. All reflections can be indexed as the rhombohedral symmetry structure [JCPDS No. 38e1104] [26].…”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that the tablets is suitable for future application as sputtering target. The relative density of IGZO disk was calculated based on the theoretical density of 6.38 g cm À3 by assuming a rhombohedral symmetry structure with lattice pa- [26,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 17(b) shows the carbon concentration profiles. As is true with hydrogen, the concentration of carbon in sample (B) is lower than that in sample (A), and this result suggests that the concentration should be approximately 10 19 atoms/cm 3 or lower for high crystallinity. That is, the amount of impurities in a film should be minimized to form a high-quality CAAC-IGZO film.…”
Section: Why Is Such a Crystal Morphology Formed?mentioning
confidence: 79%
“…A strong (009) peak appears at 2ª = 31°, which is the same as that for IGZO(009) observed from CAAC-IGZO. 10) Figure 8 shows electron backscatter diffraction (EBSD) patterns of the IGZO target. This target does not have an amorphous structure and is polycrystalline.…”
Section: Why Is Such a Crystal Morphology Formed?mentioning
confidence: 99%